Heart rate-based indices to detect parasympathetic hyperactivity in functionally overreached athletes. A meta-analysis - Manresa-Rocamora, A.; Flatt, A. A.; Casanova-Lizón, A.; Ballester-Ferrer, J. A.; Sarabia, J. M.; Vera-Garcia, F. J.; Moya-Ramón, M. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Investigations into the sensitivity of heart rate-(HR) derived indices for tracking parasympathetic nervous system (PNS) changes in functionally overreached (F-OR) endurance-trained athletes have produced equivocal findings. Lack of clarity may be a result of methodological inconsistencies. Therefore, the aims of this systematic review and meta-analysis were (a) to determine the sensitivity of resting and post-exercise vagal-related HR variability (HRV) and HR recovery (HRR) indices to detect PNS modulation in F-OR and non-overreached (non-OR) athletes, and (b) to investigate the influence of methodological factors on the sensitivity of HR-based indices to detect PNS hyperactivity in F-OR athletes. We searched CENTRAL, Scopus, PubMed, Embase, and Web of Science up to May 2020 for the following terms: male and female endurance-trained athletes, controlled and uncontrolled studies that carried out an overload training period, and PNS modulation measured in resting and post-exercise, pre- and post-overload training period. A random-effects model of standardized mean difference (SMD) was estimated for each outcome measure based on the training-induced fatigue status (F-OR vs non-OR athletes), and the influence of methodological issues to detect PNS hyperactivity in F-OR was assessed by subgroup analyses. Pooled analysis showed that resting vagal-related HRV indices did not detect PNS hyperactivity in F-OR athletes (SMD+ = -0.01; 95% confidence interval [CI] = -0.51, 0.50), and no statistical difference (P = .600) was found with non-OR athletes (SMD+ = 0.15; 95% CI = -0.14, 0.45). However, subgroup analysis based on HRV parameter showed a moderate statistical increase in weekly averaged HRV in F-OR athletes (SMD+ = 0.81; 95% CI = 0.35, 1.26), while isolated HRV values did not reach statistical significance (SMD+ = -0.45; 95% CI = -0.96, 0.06). We observed a moderate and statistically significant increase in HRR indices among F-OR athletes (SMD+ = 0.65; 95% CI = 0.44, 0.87), no changes for non-OR athletes (SMD+ = 0.10; 95% CI = -0.15, 0.34), and statistically significant differences between F-OR and non-OR athletes (P < .001). Insufficient data prevented meta-analysis for post-exercise vagal-related HRV indices. Our findings show that when methodological factors are considered, HR-based indices are sensitive to increased PNS modulation in F-OR.